Gambaran Kompetensi Mahasiswa Rekam Medis dan Informasi Kesehatan Universitas Esa Unggul - Nada Salsabila; Nanda Aula Rumana (Pusat Riset dan Inovasi Nasional, 2024)
Knowledge is the result of curiosity through the process of perception, especially the sense of sight and hearing of certain objects. The D-III Medical Records and Health Information Study Program is a program that prepares students skilled in managing health information management. The aim of the research is to determine the competency description of Esa Unggul University Medical Records and Health Information students. Descriptive research method with a quantitative analysis approach. The population in this study were Esa Unggul University Medical Records and Health Information students from the 2020 and 2019 regular and parallel classes with a total of 94 students. Research results: the characteristics of the majority of students were female (73.6%), student age ≤ 22 years (63.7%), the largest campus base was regular Kebon Jeruk (51.6%), the largest class of 2020 (73.6%). The results for competency in Clinical Classification Skills, Codification of Diseases and other Health Problems, and Clinical Procedures showed that the percentage of competent was 51.3%, while the percentage of incompetent was 48.7%. Competency in the Application of Health Statistics, Basic Epidemiology and Biomedicine obtained a competent percentage of 49.9% while the percentage of incompetent was 50.1%. RMIK Service Management Competency obtained a competent percentage of 50.3% while the percentage of incompetent was 49.7%. Conclusion: The number of competent Medical Records and Health Information students was 55 students and 36 students who were not competent. Suggestion: Registration officers improve and understand more in serving and conveying more precise and clear information. It is recommended to maintain and improve the quality of learning and increase student learning motivation in order to increase the percentage of competency.